2019
DOI: 10.1111/dme.14065
|View full text |Cite
|
Sign up to set email alerts
|

Associations between HbA1c and continuous glucose monitoring‐derived glycaemic variables

Abstract: Aims To identify clinically useful associations between HbA1c levels and various continuous glucose monitoring‐derived metrics. Methods We retrospectively analysed end‐of‐study HbA1c levels and >2 weeks of continuous glucose monitoring data collected from 530 adults with Type 1 diabetes or insulin‐requiring Type 2 diabetes during four randomized trials. Each trial lasted ≥24 weeks and provided central laboratory end‐of‐study HbA1c levels and continuous glucose monitoring data from the preceding 3 months. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 21 publications
(22 reference statements)
0
34
1
1
Order By: Relevance
“…The TIR and HbA1c values in our study (55.8% and 7.7%, respectively) and the only moderate correlation between both (r=-0.53) are in line with this. Remarkably, the correlation between TIR and HbA1c is apparently weaker in our than in other datasets, which have reported correlations ~0.75 (Beck et al 2019 21 ; and also the correlation TIR-MBG in our cohort (r=-0.81) appears to be somewhat weaker than in other studies (r=-0.92 (21); r=-0.93 (26)). This is probably in part explained by the higher GV in our cohort (30), with more hypoglycaemia (%-time<70 mg/dl: 9.7%) and a relatively high mean CV% (43.5%) as compared to those other cohorts.…”
Section: Time In Range: "Yes Please But Do Not Forget About Hypoglyccontrasting
confidence: 95%
See 1 more Smart Citation
“…The TIR and HbA1c values in our study (55.8% and 7.7%, respectively) and the only moderate correlation between both (r=-0.53) are in line with this. Remarkably, the correlation between TIR and HbA1c is apparently weaker in our than in other datasets, which have reported correlations ~0.75 (Beck et al 2019 21 ; and also the correlation TIR-MBG in our cohort (r=-0.81) appears to be somewhat weaker than in other studies (r=-0.92 (21); r=-0.93 (26)). This is probably in part explained by the higher GV in our cohort (30), with more hypoglycaemia (%-time<70 mg/dl: 9.7%) and a relatively high mean CV% (43.5%) as compared to those other cohorts.…”
Section: Time In Range: "Yes Please But Do Not Forget About Hypoglyccontrasting
confidence: 95%
“…HbA1c is widely used to assess glycaemic control because of its associations with various important outcomes (1,24) and remains valuable as it still associates with the overall risk for complications (6). However, our results confirm that HbA1c does not provide information on hypoglycaemia or GV (22,25,26), as patients can fluctuate differently throughout the day while displaying similar HbA1c (14,25). Hence, a favourable HbA1c value alone DOI:10.4158/EP-2020-0293 © 2020 AACE.…”
Section: Glycaemic Control: Ready To Be Redefined?mentioning
confidence: 61%
“…Compared with HbA1c measurement, the TIR offers more sensitive and accurate data: TIR assessment can record hypo-or hyper-glycemic events at any time, and dynamic glucose profiles and glycemic variations can be observed [4,5,13], which cannot be obtained on HbA1c assessment. Several reports have indicated that TIR is highly correlated with HbA1c levels [14][15][16], suggesting that TIR has potential value as a novel and promising metric in assessing not only short-term glycemic control but also the risk for diabetes complications in individuals with diabetes [1]. A cross-sectional study has demonstrated the association of current retrospective 3-day TIR with varying degrees of retinopathy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Relationship between CGM-derived glycemic variables and the corresponding HbA1c levels were also found by analyzing individual-level data from four randomized clinical trials [27]. Those lasted ≥ 24 weeks, had end-ofstudy HbA1c levels and at least 2 weeks of continuous glucose monitoring data collected from 530 adults with T1DM and insulin-requiring T2DM.…”
Section: Main Textmentioning
confidence: 98%